The Influence of Adding Kaliandra Flour on The Carcass and Abdomen Fat of Broiler Chickens - Brillyanto, Arga Dahana; Yakin, Engkus Ainul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The addition of alternative feed ingredients is one of the ongoing efforts to improve the quality and efficiency of broiler production, as it is one of the sources of animal protein that the community consumes in large quantities. Kalandra flour, which is known to have bioactive chemicals that can affect the performance and body composition of broiler chickens, is one possible feed item that can be utilized.The purpose of this study is to ascertain how adding calliandra flour affects the carcass and belly fat of broiler chickens. The study was carried out in Mangunharjo village, Jatipurno District, Wonogiri Regency, between March 21 and April 26, 2025. Four treatments and four replications were used in this experiment, which employed a completely randomized design (CRD). Each replication included four broiler chickens, for a total of 64 DOC. The following were the research treatments: P0: complete control feed; P1: complete control feed plus 1% calliandra flour; P2: complete control feed plus 3% calliandra flour; and P3: complete control feed plus 5% calliandra flour. Carcass weight, carcass percentage, and abdominal fat weight and percentage were the factors that were observed. Carcass weight, carcass percentage, and abdominal fat weight and percentage did not change significantly (P>0.05), according to the data. According to the study's findings, broiler chickens' carcass weight, carcass percentage, and abdominal fat weight and percentage were not significantly impacted by the addition of calliandra flour up to 5%.